A Model Simulation of the Adaptive Evolution through Mutation of the Coccolithophore Emiliania huxleyi Based on a Published Laboratory Study - Denman, Kenneth L. (Frontiers in Marine Science, 2017)
We expect the structure and functioning of marine ecosystems to change over this century in response to changes in key ocean variables associated with a changing climate. Organisms with generation times from years to decades have the capacity to adapt to changing environmental conditions over a few generations by selecting from existing genotypes/phenotypes, but it is unlikely that evolution through mutation will be a major factor for organisms with generation times of years to decades. However, phytoplankton and other microbes, with generation times of days or less, experience hundreds of generations each year, allowing the possibility for favorable mutations (i.e., those that produce organisms with fitness maxima nearer to the environmental conditions at that time) to dominate existing genotypes and survive in a changing climate. Several laboratories have grown phytoplankton cultures for hundreds to thousands of generations and demonstrated that they have changed genetic makeup. In particular Schlüter et al (2014) grew replicates derived from a single cell of Emiliania huxleyi, a coccolithophorid with broad geographical and thermal range, for 3 years (~1250 generations) at 15°C, and then for a year at 26.3°C, near their upper thermal limit. During the last year the intrinsic growth rate increased more or less linearly, which the authors attribute to genetic mutation. Here we simulate genetic mutation of a single trait (intrinsic growth rate), both for the control phase and the warm phase of their study. We consider sensitivities to frequency of mutation, changes with temperature in intrinsic growth rate, and use the experimental setup and results to place constraints on the way mutations occur. In particular, all numerical experiments with mutation result in a lag time ~30-140 generations before a significant increase in realized growth rate occurs. This lag after a favorable mutation results from the number of generations required for a single favorable mutant cell to reach a significant fraction of the ~105 cells in the culture. A numerical experiment that includes a simple plastic response formulation shows that plasticity could remove this lag and yield results more in agreement with those observed in the laboratory study.